Investigating the feasibility of a patient feedback tool to improve safety in Australian primary care: a study protocol. Issue 5 (5th May 2019) - Hernan, Andrea L; Kloot, Kate; Giles, Sally J; Beks, Hannah; McNamara, Kevin; Binder, Marley J; Versace, Vincent
Abstract : Introduction: Patients are a valuable source of information about ways to prevent harm in healthcare, and can provide feedback about the factors that contribute to safety incidents. The Primary Care Patient Measure of Safety (PC PMOS) is a novel and validated tool that captures patient feedback on safety and can be used by primary care practice teams to identify and prevent safety incidents. The aim of this study is to assess the feasibility of PC PMOS as a tool for data-driven safety improvement and monitoring in Australian primary care. Methods and analysis: Feasibility will be assessed using a mixed-methods approach to understand the enablers, barriers, acceptability, practicability, intervention fidelity and scalability of C PMOS as a tool for safety improvement across six primary care practices in the south-west region of Victoria. Patients over the age of 18 years attending their primary care practice will be invited to complete the PC PMOS when presenting for an appointment. Staff members at each practice will form a safety improvement team. Staff will then use the patient feedback to develop and implement specific safety interventions over a 6-month period. Data collection methods during the intervention period includes audio recordings of staff meetings, overt observations at training and education workshops, reflexive researcher insights, document collection and review. Data collection postintervention includes patient completion of the PC PMOS and semistructured interviews with staff. Triangulation and thematic analysis techniques will be employed to analyse the qualitative and content data. Analysis methods will use current evidence and models of healthcare culture, safety improvement and patient involvement in safety to inform the findings. Ethics and dissemination: Ethics approval was granted by Deakin University Human Ethics Advisory Group, Faculty of Health (HEAG-H 175_2017). Study results will be disseminated through local and international conferences and peer-reviewed publications.